PENGARUH KINERJA KEUANGAN, GOOD CORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SUB SEKTOR TELEKOMUNIKASI YANG TERDAFTAR DI BEI PERIODE 2019-2021. - Rosyada, Fina; Ika Prajawati, Maretha (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2022)
This study aims to ascertain how firm value is affected by GCG, CSR, and financial performance.With the increasing interest of investors in the company's shares, this study's findings are anticipated to benefit the business.Telecommunications companies that have been registered on the IDX for the 2019-2021 period make up the population used in this study.A sample of six businesses that meet a number of predetermined criteria is used in this study.The data are processed using SmartPLS 3 software, which includes an analysis of the validity test and a reliability test using an inner model.According to the findings of this study, firm value is negatively impacted by GCG and financial performance, whereas firm value is positively impacted by the CSR variable.